2014
DOI: 10.3109/0142159x.2014.886014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adopting a newly developed blueprinting method and relating it to item analysis on students’ performance

Abstract: The method adopted by using the newly developed blueprinting method and relating it to item analysis results has positive impact on the validity and reliability of students' performance results and their satisfaction in relation to intended learning outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…The primary goal of assessment via examination is to accurately measure student achievement of desired knowledge and competencies, which are generally articulated through learning objectives. 1,2 For students, locally developed examinations convey educational concepts and topics deemed important by faculty members, which allows students to interact with those concepts and receive feedback on the extent to which they have mastered the material. 3,4 For faculty members, results provide valuable insight into how students are thinking about concepts, assist with identifying student misconceptions, and often serve as the basis for assigning course grades.…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of assessment via examination is to accurately measure student achievement of desired knowledge and competencies, which are generally articulated through learning objectives. 1,2 For students, locally developed examinations convey educational concepts and topics deemed important by faculty members, which allows students to interact with those concepts and receive feedback on the extent to which they have mastered the material. 3,4 For faculty members, results provide valuable insight into how students are thinking about concepts, assist with identifying student misconceptions, and often serve as the basis for assigning course grades.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al noted that adequate resources are not always available even at the university level to ensure the valid and reliable assessment of clinical competence in the United Kingdom [ 7 ]. Building upon earlier approaches, we proposed a methodology especially suited to programs constrained by program duration relative to a large number of objectives and seemingly endless numbers of possible test questions [ 3 , 8 ]. Based upon the authors’ experience, the 50-item multiple-choice exam is a fairly common fixture in prehospital professional development examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment blueprinting also offers advantages beyond its reported enhancement of content validity in examinations [ 2 ]. Ahmad et al recently reported that their blueprinting methods, which were somewhat similar to our approach, led to improved student outcomes as measured by test scores and self-reported student satisfaction measures [ 8 ]. Furthermore, in light of the potential variability in the construction of assessment blueprints, we concur with these authors and recommend that each testing entity should consider the educational complexity and duration of their programs and courses and choose a blueprinting method best suited to ensuring content validity for each instance of testing.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that blueprinting of assessment methods not only increases their reliability and validity, but helps in student's performance result and satisfaction. (Ahmad & Hamed, 2014).…”
Section: Figure 2: Comparison Of Percentage Scores Of Pre-test and Pomentioning
confidence: 99%